1997
DOI: 10.1002/(sici)1097-0339(199703)16:3<214::aid-dc4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration of subacute granulomatous thyroiditis (De Quervain's thyroiditis): A clinico-cytologic review of 36 cases

Abstract: Although subacute granulomatous thyroiditis (SGT) is usually diagnosed clinically, there are other thyroid conditions that must be ruled out. This task is achieved by means of fine‐needle aspiration (FNA). In retrospect, the clinical and cytologic findings seen in 36 SGT cases are reassessed with a view to deciding which findings are most reliable for reaching a confident cytologic diagnosis. These are: the simultaneous presence in the same aspirate of the following cells: 1) follicular cells with intravacuola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
2
24
0
1
Order By: Relevance
“…21 The aspirate of SGT usually dis- Our study was performed with Papanicolou stain and we were able to compare the reported cytologic features. 10,21 with those of our cases. Our cytologic results…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…21 The aspirate of SGT usually dis- Our study was performed with Papanicolou stain and we were able to compare the reported cytologic features. 10,21 with those of our cases. Our cytologic results…”
Section: Discussionsupporting
confidence: 85%
“…The cytologic literature on SGT is relatively rare, but the cytologic features of SGT has been well described. 1,[4][5][6]10,21 One report summarized the key cytologic features of SGT with performing Giemsa staining. 10 and after that, another report has been published that used Papanicolou stain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytomorphology of SAT shows mixed inflammatory cells with follicular cell degeneration and transformation, many epithelioid cells (with granulomas) and multinucleated cells [9] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Eine Feinnadelpunktion der Schilddrü-se ergibt klassischerweise nicht-verkäse-nde Granulome mit mehrkernigen Riesenzellen vom Fremdkörpertyp, fibrotische Gewebestränge und eine Infiltration durch Immunzellen [14,17]. Die Wertigkeit einer zytopathologischen Diagnostik ist jedoch umstritten [18,19], da falschpositive Ergebnisse nicht selten [20] und gerade in der Akutphase der Erkrankung häufig die charakteristischen histologischen Merkmale nicht nachweisbar sind [21].…”
Section: Diagnostikunclassified